Kemampuan Spasial Siswa dalam Menyelesaikan Soal Geometri Berdasarkan Level Berpikir Van Hiele - Munawaroh, Siti Mukarromah Halimatul; Masrurotullaily, Masrurotullaily; Septiadi, Dimas Danar (Lembaga Intelektual Muda (LIM) Maluku, 2024)
Spatial ability is an ability to represent an abstract concept into a two/three-dimensional visual form and make changes to a geometric shape. The aim of this study is to describe students' spatial abilities in solving geometrical problems of flat-sided geometry based on van Hiele’s level of thinking, namely visualization, analysis, abstraction, and formal deduction. This research was conducted in class XI SMK Al-Azhar and resulted in student with van Hiele’s level of visualization have spatial abilities on indicators of spatial perception and spatial relations. Student with van Hiele’s level of analysis have spatial abilities on indicators of spatial perception and visualization as well as spatial relations. Student with van Hiele’s level of abstraction have spatial abilities on indicators of spatial visualization and spatial relations. Student with the van Hiele’s level of formal deduction have spatial abilities on indicators of spatial perception and visualization as well as spatial relations